In vitro evaluation of cytomegalovirus‐specific hyperimmune globulins vs. standard intravenous immunoglobulins. Issue 1 (12th March 2015) - Miescher, S. M.; Huber, T. M.; Kühne, M.; Lieby, P.; Snydman, D. R.; Vensak, J. L.; Berger, M.
<x xml:space="preserve">Abstract</x> Background and Objectives To evaluate standard intravenous immunoglobulin (IVIG) as an alternative to intravenous cytomegalovirus hyperimmune immunoglobulin (CMVIG) for prophylaxis and therapy of cytomegalovirus (CMV) disease, we measured the ELISA and neutralizing titres of CMV‐specific antibodies in CMVIG and IVIG preparations. Materials and Methods Anti‐CMV‐IgG ELISA and neutralizing titres (fibroblast‐based test) in CMVIG CG (Cytogam®, n = 20), CMVIG CT (Cytotect® CP, n = 3), IVIG P (Privigen®, n = 32) and IVIG K/G (Kiovig®/Gammagard®, n = 5) were compared, and IgG subclasses 1–4 were determined by nephelometry. Results Cytomegalovirus hyperimmune immunoglobulins contained more than fourfold higher CMV ELISA and CMV‐neutralizing activity per gram of IgG than the standard IVIGs. Pooled data for all four products showed a significant correlation between anti‐CMV‐IgG ELISA and neutralizing titres (r = 0·93, P < 0·001). There was a good correlation between the IgG3 content and CMV‐neutralizing antibodies amongst lots of CMVIGs (r = 0·91, P = 0·01), but this did not extend to the IVIGs. CMVIG CG contained the highest CMV‐neutralizing activity (3497 ± 395 PEIU/g IgG) of any product tested. Conclusion The higher anti‐CMV neutralization capacity of CMVIG per gram of IgG vs. standard IVIG suggests that standard IVIGs are not equivalent to or interchangeable with CMVIG.